An Historical and Statistical Account of New South Wales, Both as a Penal Settlement and as a British Colony, Volume 1 - Lang, John Dunmore (Cambridge library collection. History of Oceania, 1834)
The first prominent advocate of Australian republicanism, Scottish-born John Dunmore Lang (1799–1878) is an important figure in the history of his adopted country. This two-volume work, originally published in 1834, presents a series of chapters illustrating Australia's history and its condition in his own time. Written during a voyage from New South Wales to Britain in 1833, the book promotes what Lang deems to be the best interests of the New South Wales colony, by encouraging the emigration 'of reputable families and individuals to its territory'. Volume 1 sets out the historical background and discovery of the coastal areas, leading to the establishment of the New South Wales British colony, and presents accounts of its condition and progress under various governments. The reader will be mindful of Lang's aim in writing the work - to tell the truth 'fully and fearlessly' in order to secure Australia's general welfare and advancement